2012
DOI: 10.1111/j.1742-6723.2012.01535.x
|View full text |Cite
|
Sign up to set email alerts
|

Organ and tissue donation‐related attitudes, education and practices of emergency department clinicians in Australia

Abstract: Objective:The ED is emerging as a priority for efforts to improve rates of organ and tissue donation (OTD) in Australia, but little is known of ED clinicians' attitudes, education or practices in the area. We aimed to determine the attitudes and OTD-related educational background and practices of Australian ED clinicians. Methods:This was a national cross-sectional survey of members of the Australasian College for Emergency Medicine (ACEM) and the College of Emergency Nursing Australasia (CENA); online questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
34
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 19 publications
4
34
0
2
Order By: Relevance
“…Moreover, insufficient education provided to health professionals on aspects of organ donation and transplantation continues to be reported in the literature as a global issue not only in the nursing arena but amongst medical and surgical groups (Collins, 2005;Jelinek et al, 2012;Kim et al, 2004;Marck et al, 2012;Melo et al, 2011;Meyer et al, 2012;Rios et al, 2007). Participants in this current study reported that education was lacking and that there was no emphasis on preparing perioperative nurses for the emotional aspects of participation in organ procurement surgery.…”
Section: Discussionmentioning
confidence: 54%
“…Moreover, insufficient education provided to health professionals on aspects of organ donation and transplantation continues to be reported in the literature as a global issue not only in the nursing arena but amongst medical and surgical groups (Collins, 2005;Jelinek et al, 2012;Kim et al, 2004;Marck et al, 2012;Melo et al, 2011;Meyer et al, 2012;Rios et al, 2007). Participants in this current study reported that education was lacking and that there was no emphasis on preparing perioperative nurses for the emotional aspects of participation in organ procurement surgery.…”
Section: Discussionmentioning
confidence: 54%
“…The combination of indifference and negativity, amongst HCPs, is inseparably linked with limitation of knowledge and awareness of the ODT process (Ahlawat et al., ) as well as a fear of the inevitability of death (Rios Zambudio et al., ). In spite of some HCPs’ positivity and favourability towards ODT, it is widely reported in the literature that, very often, these do not translate into HCPs’ willingness to donate their own organs for the purpose of transplantation (Chernenko, Jensen, Newburn‐Cook, & Bigam, ; Demir, Selimen, Yildirim, & Kucuk, ; Jelinek, Marck, Weiland, Neate, & Hickey, ; Pont Castellana et al., ; Rios Zambudio et al., ). HCPs’ unwillingness to donate organs for transplantation is, of course, not the focus of this review.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, some HCPs demonstrated positive attitudes towards ODT and an exhibited willingness to donate their organs (e.g., by enrolling on an organ donation register and/or by carrying donor cards) and possessed the tendency to identify potential donors. They were also most likely to activate the organ donation process by seeking and obtaining consent from potential donor families (Abidin et al., ; Alsaied, Bener, Al‐Mosalamani, & Nour, ; Chernenko et al., ; Jelinek et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…The need for education has been shown to be high (21%) in hospital employees [23]. Education is requested by health professionals, can correct false information and might lead to higher organ donation rates [24-26]. However, also legitimate reasons for their concerns, such as problems in accepting the brain death concept or organ procurement procedures might be present.…”
Section: Discussionmentioning
confidence: 99%